PENGGUNAAN MEDIA SOSIAL INSTAGRAM SCHOLARS_IG SEBAGAI MEDIA PROMOSI DIGITAL PROGRAM BEASISWA - Izzatul Chumairoh; Sandy Permata (Program studi Ilmu Komunikasi Fakultas Ilmu Komunikasi Universitas Persada Indonesia YAI, 2021)
Social media is a platform that can influence many people. Many people use it not only as a place of remembrance that can be seen by the public but can also be used to provide information, knowledge and tucked in it for promotional media. Instagram is one of the platforms that is considered very effective in providing the latest information, almost everyone has the Instagram social media. The use of Instagram Scholars_Ig Social Media can attract followers to join the scholarship program online. The purpose of this study was to identify and explain the use of Instagram social media